Molecular and serological investigation of cat viral infectious diseases in China from 2016 to 2019. Issue 6 (2nd July 2020) - Liu, Caihong; Liu, Yuxiu; Qian, Peng; Cao, Yujiao; Wang, Jie; Sun, ChunYan; Huang, Baicheng; Cui, Ningning; Huo, Ningning; Wu, Hongchao; Wang, Lingxiao; Xi, Xiangfeng; et al.
Abstract: In order to analyse the prevalence of cat viral diseases in China, including feline parvovirus (FPV), feline calicivirus (FCV), feline herpesvirus 1 (FHV‐1), feline leukaemia virus (FeLV), feline immunodeficiency virus (FIV) and feline infectious peritonitis virus (FIPV), a total of 1, 326 samples of cats from 16 cities were investigated from 2016 to 2019. Collectively, 1, 060 (79.9%) cats were tested positive for at least one virus in nucleotide detection, and the positive rates of cat exposure to FeLV, FPV, FHV‐1, FCV, FIV and FIPV were 59.6%, 19.2%, 16.3%, 14.2%, 1.5% and 0.5%, respectively. The prevalence of FHV‐1 and FPV was dominant in winter and spring. Cats from north China showed a higher positive rate of viral infection than that of cats from south China. The virus infection is not highly correlated with age, except that FPV is prone to occur within the age of 12 months. In the serological survey, the seroprevalences of 267 vaccinated cats to FPV, FCV and FHV‐1 were 83.9%, 58.3% and 44.0%, respectively. Meanwhile, the seroprevalences of 39 unvaccinated cats to FPV, FCV and FHV‐1 were 76.9% (30/39), 82.4% (28/34) and 58.6% (17/29), respectively. This study demonstrated that a high prevalence of the six viral diseases in China and the insufficient serological potency of FCV and FHV‐1 remind the urgency for more effective vaccines.